2006
DOI: 10.1002/hep.21190
|View full text |Cite
|
Sign up to set email alerts
|

Cryoglobulinemia is associated with steatosis and fibrosis in chronic hepatitis C†

Abstract: The relationship between cryoglobulin and severity of liver lesions is debated. No study has focused on the relationship between cryoglobulin, liver steatosis, and fibrosis. The aim of this study was to determine the relationship between cryoglobulins and liver lesions (necroinflammation, fibrosis, and steatosis) in patients with hepatitis C virus (HCV) infection. Four hundred and thirty-seven consecutive patients with untreated chronic hepatitis C who had been admitted for liver biopsy were included in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 44 publications
4
53
0
4
Order By: Relevance
“…Therefore, the finding that an enhanced frequency and function of CD4ϩ CD25 high cells was associated with a lower degree of HCV-associated liver inflammation (39,49), as well as the finding that activated Treg cells in patients with chronic HCV infection suppressed effector cell activity in a non-antigen-specific manner (41), may both suggest a beneficial role of Treg cells in reducing immunemediated bystander injury in chronic HCV infection. In this context, it is interesting to note that patients with HCV-induced MC vasculitis have more-severe liver injury, with a higher frequency of cirrhosis, compared with patients with chronic HCV infection without MC (50,51). In the present study, we demonstrated that autoimmune manifestations induced by HCV are associated with lower Treg cell levels.…”
supporting
confidence: 54%
“…Therefore, the finding that an enhanced frequency and function of CD4ϩ CD25 high cells was associated with a lower degree of HCV-associated liver inflammation (39,49), as well as the finding that activated Treg cells in patients with chronic HCV infection suppressed effector cell activity in a non-antigen-specific manner (41), may both suggest a beneficial role of Treg cells in reducing immunemediated bystander injury in chronic HCV infection. In this context, it is interesting to note that patients with HCV-induced MC vasculitis have more-severe liver injury, with a higher frequency of cirrhosis, compared with patients with chronic HCV infection without MC (50,51). In the present study, we demonstrated that autoimmune manifestations induced by HCV are associated with lower Treg cell levels.…”
supporting
confidence: 54%
“…The prognosis seems more severe in HBV-PAN, with 35% of deaths compared to 10% in patients with HCV infection. HCV-related vasculitis does not bear specific virologic features in term of genotype, viral load, or phylogenetic analysis (31)(32)(33). In contrast, in HBV-PAN most cases are associated with high levels of viral replication identified by high-serum HBV-DNA levels and hepatitis B antigen positivity, promoting the persistence of viral immune complexes in antigen excess (34).…”
Section: Pan-type Vasculitis Associated With Hcvmentioning
confidence: 99%
“…The evolution was fatal and the patient died a few hours after admission to intensive care, this reinforces the data of the literature concerning the severity of the central neurological manifestation. In addition, several cohort studies have shown the existence of epidemiological, clinical and biological factors strongly associated with the production of mixed cryoglobulinemia during chronic hepatitis C virus infection, including female sex, advanced age , Genotype 2 or 3 and extensive liver fibrosis [8,9]. Two of these factors are present in our case and which have led to the diagnosis of an extra-hepatic disorders of hepatitis C.…”
Section: Discussionmentioning
confidence: 53%